Implementation of PAUD Unit Accreditation in South Padangsidimpuan City - Revi Hervita Suryani Nasution; Khadijah Khadijah; Ali Imran Sinaga (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
School accreditation is school assessment activities that are carried out systematically and comprehensively through self-evaluation and external evaluation (visitation) activities to determine the feasibility and performance of the school. Accreditation has a meaning as a comprehensive assessment process of the appropriateness and performance of an institution or an educational program as a form of public accountability, a self regulation tool in which schools recognize strengths and weaknesses and continuously improve strengths and improve their weaknesses. This understanding will give more meaning in the results as an acknowledgment, a school has met the specified eligibility standards. Padangsidimpuan City as one of the cities in Indonesia is not immune from the policy to carry out accreditation in each of its educational institutions or units. Some education units have carried out accreditation in the District of South Padangsidimpuan. In carrying out accreditation, the institution certainly cannot be separated from the constraints that must arise, both internal and external constraints. Government efforts to develop human resources through PAUD and PAUD education units have encouraged education units to meet eight (8) National Education Standards (SNP). In the framework of meeting these standards, the central government and regional governments prepare education units to be ready to be accredited on an ongoing and ongoing basis in the hope that the accreditation process can improve the quality of education units. Especially in the city of Padangsidimpuan, South Padangsidimpuan Subdistrict. Based on the results of the interviews. Obtained data from the Padangsidimpuan City Education Office for South Padangsidmpuan Subdistrict, with a total of 17 units, more than 50% have been accredited, 9 are accredited institutions and 8 institutions have B grades and 1 institution with a value of C. Provide an overview of the level of school performance that is used as a tool for coaching, developing and improving schools both in terms of quality, effectiveness, efficiency, productivity and innovation. Providing guarantees to the public that the school has been accredited and provides educational services that meet national accreditation standards.